Academic Information Systems And PPDB Base On Web-Android - Wirhan Fahrozi; Fitriana Harahap; Fithry Tahel; Erwin Ginting; Dedek Indra Gunawan Hts (IJISTECH (International Journal of Information System and Technology), 2022)
SMA-SMK Yapim Taruna Belawan is an institution engaged in the field of education. Student registration and reporting of student assessment results at SMA-SMK Yapim Taruna Belawan is a form of service for students/students. In terms of registration, efforts are made to be more effective and for the student assessment process covering all activities in schools to be more effective and efficient by using internet technology facilities in the form of a school academic system. The academic system that is currently operating at the Yapim Taruna Belawan High School and Vocational Schools is not all computerized and cannot be accessed online. In addition, every input of academic data that is stored in the form of sheets of paper is considered less effective and efficient because the administration section will experience difficulties when it comes to recording data when making reports. So that it is hoped that a better system will be formed that can solve these problems by implementing a web-based and mobile internet technology base, so that information can be accessed boldly